Elements of Stakeholder Involvement and Performance of Rural Electrification Projects - Ainomugisha, Sarah; Mpangwire, Violah; Musiita, Benjamin (Journal of Economics and Behavioral Studies, 2024)
The research aimed to explore how different aspects of stakeholder participation correlate with the effectiveness of rural electrification projects in southwestern Uganda. Employing a cross-sectional research design, data was gathered from 32 projects as the primary unit of analysis, with a sample size of 34 projects selected from a total population of 39 rural electrification projects, determined using Krejicie and Morgan’s method from 1970. Analysis methods included Pearson correlation and regression. The findings demonstrated a statistically significant positive relationship between communication, compliance, and engagement with the performance of rural electrification projects. Regression analysis further supported these results, showing significant unstandardized coefficients for each respective dimension. Moreover, the regression model indicated that communication, compliance, and engagement, as measures of stakeholder involvement, accounted for 39.5% of the variability in rural electrification project performance in southwestern Uganda. This suggests that other factors not addressed in this study explained the remaining 60.5%. Therefore, the study suggests that comprehensive stakeholder involvement, involving clear communication before and during project implementation, adherence to regulations agreed upon by stakeholders, and active engagement of all parties at each project stage, is crucial for achieving project success.